1989
DOI: 10.3109/03009748909099926
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonography of the Adult Hip Joint

Abstract: The ultrasonographic distance between the hip joint capsule and femur was measured in 75 healthy adults. The mean distance was 5.1 (SD 0.7) mm. The shortest distance was 3.0 mm, the longest 7.0 mm. The difference between the right and left hip was 0.3 (SD 0.3, range 0-1.2) mm. No correlation was found between the ultrasonographic distance and the subjects' height, body weight, age or sex. The reproducibility of the measurement was good, and the interobserver correlation was 0.94. It is concluded that an ultras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
1
8

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(47 citation statements)
references
References 4 publications
1
37
1
8
Order By: Relevance
“…Therefore, the use of high-flux dialyzers is expected to be associated with a lower rate of complications involving the osteoarticular system (Geyo, 2001). Beta2-microglobulin concentration does not correlate with the activity of dialysis-related amyloidosis, thus serum β2-microglobulin concentration is not a diagnostic test to determine the severity of dialysis-related amyloidosis (Farrell & Bastani, 1997;Koski et al, 1989). A number of studies have confirmed that clinical symptoms of complications involving the osteoarticular system are more common in patients undergoing hemodialysis for a prolonged period of time, as well as in those with higher β2-microglobulin concentration (Barišić et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the use of high-flux dialyzers is expected to be associated with a lower rate of complications involving the osteoarticular system (Geyo, 2001). Beta2-microglobulin concentration does not correlate with the activity of dialysis-related amyloidosis, thus serum β2-microglobulin concentration is not a diagnostic test to determine the severity of dialysis-related amyloidosis (Farrell & Bastani, 1997;Koski et al, 1989). A number of studies have confirmed that clinical symptoms of complications involving the osteoarticular system are more common in patients undergoing hemodialysis for a prolonged period of time, as well as in those with higher β2-microglobulin concentration (Barišić et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Увеличение ШКР по данным УЗИ, являющееся по-казателем воспаления ТБС [9], имелось практически у ка-ждого второго нашего пациента. И этот признак, так же как и клиническая симптоматика коксита, в первую оче-редь был значимо связан с индексами активности болезни, хотя и уровень СРБ был выше при наличии коксита, под-твержденного с помощью УЗИ.…”
Section: таблицаunclassified
“…[6], которые анализировали материалы регистров больных АС, частота коксита составляет от 24 до 36% в зависимости от длитель-ности АС, а потребность в эндопротезировании -8%. В то же время, по данным многоцентрового одномоментного исследования, проведенного в России [9], клинические признаки поражения ТБС наблюдались в 56% случаев, и в 7% случаев требовалось эндопротезирование сустава. Возникает вопрос: почему при такой высокой частоте клинически выявляемого поражения данного сустава только меньшая часть больных нуждается в хирургической помощи?…”
unclassified
See 1 more Smart Citation
“…Ultrasonography has a very important advantage over other imaging methods because it allows the concomitant visualization of the target structure, the needle penetration and tip positioning as well as the drug deposition (Bradley MJ, 2001). Indeed, musculoskeletal ultrasound evaluation is an accurate and reliable method in depicting articular and periarticular lesions, has no radiation, is cheap and quick to perform and allows repeated examinations at baseline and during follow up (Bierma-Zeinstra et al, 2001;Koski JM et al, 1989;Iagnocco A et al, 2006;Qvistgaard E et al, 2001). Moreover, a modular flexible training strategy to achieve competence in diagnostic as well as in interventional musculoskeletal ultrasound showed a fast learning curve among rheumatologists, thus encouraging its employment in daily practice (Atchia I et al, 2007).…”
Section: Introductionmentioning
confidence: 99%